Fragmentasi Hukum Internasional dan Ketimpangan Akses Teknologi dalam Perlindungan Keanekaragaman Hayati di Luar Yurisdiksi Nasional (BBNJ) di Era Globalisasi - Muhammad Arsy Perwira Witono (PT. Hasba Edukasi Mandiri, 2025)
Marine biodiversity in areas beyond national jurisdiction (Biodiversity Beyond National Jurisdiction/BBNJ) plays a critical role in maintaining global ecological balance and supporting the sustainable use of marine genetic resources. However, its protection and governance face significant challenges in the era of globalization, particularly due to the fragmentation of international legal regimes and persistent inequalities in access to technology among states. This article aims to examine how fragmentation within international law, weak integration between science and policy, and disparities in technology transfer and benefit-sharing mechanisms undermine the effective protection of BBNJ. Employing a normative juridical approach from the perspective of international law, this study analyzes international agreements, global policy frameworks, and relevant scholarly literature on BBNJ governance. The analysis reveals that the absence of an integrated international legal framework has resulted in overlapping mandates and weak institutional coordination, while developing countries remain disadvantaged in terms of access to scientific data, technological capacity, and participation in marine research. These inequalities have led to imbalances in the distribution of benefits derived from marine genetic resources and limited the involvement of developing states in global decision-making processes. This article underscores the urgency of strengthening a more inclusive, equitable, and science-based international legal framework, alongside effective technology transfer mechanisms, as essential prerequisites for sustainable and just governance of BBNJ in the context of globalization.